Photodiagnostic services in the UK and Republic of Ireland: a British Photodermatology Group Workshop Report. (13th September 2021) - Ibbotson, S.H.; Allan, D.; Dawe, R.S.; Eadie, E.; Farr, P.M.; Fassihi, H.; Fedele, F.; Ferguson, J.; Fityan, A.; Freeman, P.; Fullerton, L.; Goulden, V.; et al.
Abstract: Background: Photodiagnostic investigations are essential for the accurate diagnosis of abnormal cutaneous photosensitivity and provide important information for the management of patients with photodermatoses (cutaneous photosensitivity disorders). Although photodiagnosis has been undertaken since the early 1970s, specialist services in the United Kingdom (UK) and Republic of Ireland are limited and there is no formal guidance on diagnostic approach. Indeed, there is a limited literature in this area of methodology and diagnostic practice. Objectives: The primary objective was to undertake a British Photodermatology Group Workshop to review the role and activities of specialist centres in the UK and Republic of Ireland in order to ascertain whether there were consensus practices. Secondary objectives were to identify key priorities for service, training and research. Methods: An initial detailed survey review of current activities was undertaken prior to the Workshop and data from this survey were used to inform discussion at the Workshop, which was attended by key photodermatology experts from the UK and Republic of Ireland. Results/Conclusions: We have undertaken a detailed review of current Photodiagnostic Services in the UK and Republic of Ireland and report on our findings from the 12 centres and we have identified key areas of consensus practice. This is an important step in the process of standardising and optimising procedures and protocols and defining minimum clinical standards for photodiagnostic investigations, which are of such diagnostic importance in Dermatology.